Implementasi Layanan Bimbingan Kelompok Anak Berkebutuhan Khusus Tunanetra di SKHN 02 Kota Serang - Ramadan; Ijaji, Rahmadani; Ninda Falah Yuniar; Septiyani Putri Rahma Dewi; Arga Satrio Prabowo (Sociocouns: Journal of Islamic Guidance and Counseling, 2025)
This research aims to describe the implementation of group counseling services for visually impaired children with special needs at State Special School (SKHN) 02 in Serang City. Group counseling services are one of the guidance and counseling strategies that aim to help students develop social skills, independence, and self-confidence. The research used a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results showed that the implementation of group guidance services at SKHN 02 Serang City was carried out through the stages of planning, implementation, and evaluation. In practice, guidance counselors face obstacles such as limited media, time constraints, and the heterogeneity of visually impaired students' abilities. However, this service has been proven to help students build effective communication, increase self-confidence, and practice social independence. These findings indicate that group guidance can be a strategic alternative in optimizing the potential of visually impaired children in inclusive schools and special schools.